Association of Broiler Litter Microbiome Composition and Campylobacter Isolation - Valeris-Chacin, Robert; Pieters, Maria; Hwang, Haejin; Johnson, Timothy J.; Singer, Randall S. (Frontiers in Veterinary Science, 2021)
Infection with Campylobacter species is one of the leading causes of bacterial diarrhea in humans in the US. Chickens, which become colonized on the farm, are important reservoirs of this bacterium. Campylobacter can establish itself in the broiler house via a variety of sources, can survive in the litter of the house, and possibly persist over successive flock cycles. However, the role of the broiler litter microbiome on Campylobacter persistence is not clear. A matched case-control study was conducted to determine whether the broiler litter microbiome composition was associated with Campylobacter isolation within the broiler house. Flocks were classified as cases when either C. jejuni or C. coli was isolated in boot sock samples, or as controls otherwise. Case and control flocks were matched at the broiler house level. Composite broiler litter samples were collected and used for DNA extraction and 16S rRNA gene V4 region sequencing. Reads were processed using the DADA2 pipeline to obtain a table of amplicon sequence variants. Alpha diversity and differential bacterial relative abundance were used as predictors of Campylobacter isolation status in conditional logistic regression models adjusting for flock age and sampling season. Beta diversity distances were used as regressors in stratified PERMANOVA with Campylobacter isolation status as predictor, and broiler house as stratum. When Campylobacter was isolated in boot socks, broiler litter microbiome richness and evenness were lower and higher, respectively, without reaching statistical significance. Campylobacter isolation status significantly explained a small proportion of the beta diversity (genus-level Aitchison dissimilarity distance). Clostridium and Anaerostipes were positively associated with Campylobacter isolation status, whereas Bifidobacterium, Anaerosporobacter, and Stenotrophomonas were negatively associated. Our results suggest the presence of bacterial interactions between Campylobacter and the broiler litter microbiome. The negative association of Campylobacter with both Bifidobacterium and Anaerosporobacter in litter could be potentially exploited as a pre-harvest control strategy.